A NOTE ON THRESHOLD FACTOR LEVEL(S) AND STONE-GEARY TECHNOLOGY. (21st July 2015) - BEATTIE, BRUCE R.; ARADHYULA, SATHEESH
Abstract: This article proposes the parsimonious Stone-Geary utility function from consumer choice theory as a production function model. The viability of the threshold input idea is empirically demonstrated for irrigation water (and in the case of nitrogen, a "gratis" threshold) using two field trials from the famous Hexem-Heady data sets. The implications of the Stone-Geary model for tractable U-shaped average variable cost and for factor demand and product supply are explored.